2021
DOI: 10.18632/aging.202387
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RNA-binding protein SNRPA1 for prognosis in prostate cancer

Abstract: Prostate cancer is one of the deadliest cancers in men. RNA-binding proteins play a critical role in human cancers; however, whether they have a significant effect on the prognosis of prostate cancer has yet to be elucidated. In the present study, we performed a comprehensive analysis of RNA sequencing and clinical data from the Cancer Genome Atlas dataset and obtained differentially expressed RNA-binding proteins between prostate cancer and benign tissues. We constructed a protein-protein interaction network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…34 Although we did not find potential target-miRNAs of XLOC_008672 (data not shown), XLOC_008672 was identified to interact directly with RNA-binding protein SNRPA via a series of bioinformatics analysis and molecular biology experiments. Previous studies have elucidated that SNRPA is not only involved in the pre-mRNA splicing process, it can also act as an oncogene in different tumor types, 35,36 and we previously reported that SNRPA promotes tumor cell growth via NGF in GC. 37 The findings in the current work showed another new mechanism in GC development: that SNRPA can be associated with XLOC_008672 and co-regulate the stabilization of G3BP1 mRNA for the first time.…”
Section: Discussionmentioning
confidence: 87%
“…34 Although we did not find potential target-miRNAs of XLOC_008672 (data not shown), XLOC_008672 was identified to interact directly with RNA-binding protein SNRPA via a series of bioinformatics analysis and molecular biology experiments. Previous studies have elucidated that SNRPA is not only involved in the pre-mRNA splicing process, it can also act as an oncogene in different tumor types, 35,36 and we previously reported that SNRPA promotes tumor cell growth via NGF in GC. 37 The findings in the current work showed another new mechanism in GC development: that SNRPA can be associated with XLOC_008672 and co-regulate the stabilization of G3BP1 mRNA for the first time.…”
Section: Discussionmentioning
confidence: 87%
“…Yuan et al. ( 16 ) also observed the increased value of SNPRA1 in prostate cancer patients; SNRPA1 inhibition also decreased tumor cell migration and colony formation.…”
Section: Discussionmentioning
confidence: 90%
“…They discovered that the nerve growth factor (NGF) was upregulated with SNRPA overexpression at the mRNA and protein levels, suggesting that NGF is probably a downstream effect in GC. Yuan et al (16) found that the SNRPA1 expression level was positively associated with Gleason score in prostate cancer (PCa). Furthermore, inhibition of SNRPA1 could result in a decrease in PCa cell migration, proliferation, and colony formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNA data are characterized by dissociation and can be used for non-invasive diagnosis and dynamic detection of disease (15). Common transcriptome, or mRNA sequencing, is the cheapest and most readily available, and is suitable for use in a wide range of cohort studies to explore general patterns in patient populations (16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%